Fire risk assessment at heritage building: a case study at school building in Ipoh Perak / Siti Nor Fatihah Mohamad Azmi - Mohamad Azmi, Siti Nor Fatihah (2016)
There are many cases of fire involving Malaysian heritage school. In the past few years, there is several irreplaceable heritage buildings has damaged because of fire. It is important to give good fire protection measures to heritage building because there are two factors that must be considered. First, the protection for occupants and visitors of the buildings and second the protection of the building fabrics and its valuable contents. This study is based on the objective which is to identify the compliances of fire safety in heritage school building and other objectives are to identify the requirement of fire safety according to the act in heritage school building. The research method use is by interviewing the responsible person for fire risk assessment in the building. The outcome based on interview session by En. Dzulkifli Bin Kassim he is a senior fire officer at fire station Ipoh, from the interview session the question, ask about the fire risk assessment, such as the importance of signage at school, the importance of mean of escape provide at school and should lead to a place of safety and should be safe to use. From the interview session also know about the importance of fire requirement provided at school and it must function well. Other than that, from interview session the occupant must know about the placement of the fire extinguishers, the occupant at the school less knowledge about fire safety requirement, hence from the interview session the fire Bridget gives suggestion that the people who responsible at school should do something for student to know them about the importance of fire safety such as talk, fire drill and so on. The second method used is a questionnaire, from the questionnaire have been passed to respondent at school like a teacher, student, parent and the other the majority answer strongly agree that the school must have a better protection system on fire safety, they also strongly agree that the school provided enough fire requirement and must function to save them from danger when fire occurs.